2020
DOI: 10.21203/rs.3.rs-36928/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calreticulin promotes EMT in pancreatic cancer via mediating Ca2+ dependent acute and chronic endoplasmic reticulum stress

Abstract: Background: Our previous study showed that calreticulin (CRT) promoted EGF-induced epithelial-mesenchymal transition (EMT) in pancreatic cancer (PC) via Integrin/EGFR-ERK/MAPK signaling. We next investigated the novel signal pathway and molecular mechanism involving the oncogenic role of CRT in PC. Methods: We investigated the potential role and mechanism of CRT in regulating intracellular free Ca2+ dependent acute and chronic endoplasmic reticulum stress (ERS)-induced EMT in PC in vitro and vivo.Results: Thap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Therefore, we hypothesized that the IRES sequence was located at the full‐length sequence (nt 1982‐nt 2281) in the VP3 gene (Figure 2E). We also confirmed that IRES activity could be increased under ER stress induced by TG as reported previously 26,31 (Figure 3). Finally, we verified that the IRES (nt 1982‐nt 2281) initiated the translation of GFP in a cap‐independent manner (Figure 4A).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we hypothesized that the IRES sequence was located at the full‐length sequence (nt 1982‐nt 2281) in the VP3 gene (Figure 2E). We also confirmed that IRES activity could be increased under ER stress induced by TG as reported previously 26,31 (Figure 3). Finally, we verified that the IRES (nt 1982‐nt 2281) initiated the translation of GFP in a cap‐independent manner (Figure 4A).…”
Section: Discussionsupporting
confidence: 92%
“…Epithelial-mesenchymal transition (EMT) is a cellular process initiated from cellular micro environment following the acquisition of mesenchymal phenotypes and the repression of epithelial features, which finally contributes to the cell invasion and metastasis of cancer, including PC [4,5]. The key characteristic of EMT is the deficiency of epithelial markers, such as E-cadherin and the gain of interstitial markers, such as Vimentin and MMPs [6]. Increasing evidence confirms the significant role of PI3K-AKT-mTOR signaling pathway and it's downstream targets (p-AKT, p-PI3K and p-mTOR) in regulating EMT process [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Yogalakshmi et al showed that PCB2 restrained ERS by downregulating mRNA levels of PERK, IRE1α, and ATF-6 and protein levels of eIF2α and XBP1 in high-calorie diet-fed rats [33]. Furthermore, we used 4-PBA and TG, the ER stress inhibitor and agonist, respectively [34,35], to assess the protective role of PCB2 in the context of PA-induced injury in HepG2 cells, indicating that ERS-dependent prevention could be involved in its protective effects. Previous and current experiments have confirmed the anti-ERS effects of PCB2 at multiple levels.…”
Section: Discussionmentioning
confidence: 99%